Prenatal and postnatal markers of severity in congenital diaphragmatic hernia have similar prognostic ability. (19th January 2016) - Werner, N. L.; Coughlin, M.; Kunisaki, S. M.; Hirschl, R.; Ladino‐Torres, M.; Berman, D.; Kreutzman, J.; Mychaliska, G. B.
Abstract: Objectives: The purpose of this study was to compare prenatal versus postnatal markers of congenital diaphragmatic hernia (CDH) severity at a single fetal‐care center. Methods: A retrospective study was performed of patients having a complete prenatal evaluation and surgical repair ( n  = 55). Observed‐to‐expected lung‐to‐head ratio (o/eLHR), observed‐to‐expected total lung volume (o/eTLV), liver position (LP), a predictive dependent variable from logistic regression of o/eLHR and liver position (o/eLHR + LP), and diaphragmatic defect size per the CDH Study Group A–D classification were plotted into receiver–operating characteristics (ROC) curves. Survival and need for extracorporeal membrane oxygenation (ECMO) were primary outcomes. Results: Survival was 69%, and ECMO utilization was 56%. Distribution was 80% left‐sided defects. In the survival ROC curve, the area under the curve (AUC) for o/eLHR was 0.73, o/eTLV 0.74, LP 0.73, o/eLHR + LP 0.78, and defect size 0.84 ( p  = 0.23). The ROC curve for ECMO support showed o/eLHR had an AUC of 0.82, o/eTLV 0.89, LP 0.79, o/eLHR + LP 0.87, and defect size 0.90 ( p  = 0.19). The AUCs were similar when only left‐sided CDH was analyzed. Conclusions: These data suggest that prenatal evaluation was equivalent to the postnatal diaphragmatic defect classification for predicting survival and need for ECMO in CDH patients. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Prenatal markers of CDH severity (lung‐to‐head ratio, MRI lung volumes, and liver position) have demonstrated prognostic accuracy but remain controversial. Hernia defect size is a popular postnatal marker of CDH severity that is well validated but requires surgical repair to be determined. What does this study add? This study demonstrates that prenatal and postnatal markers are equivalent in their ability to predict survival and need for extracorporeal life support in CDH patients.